Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Pada Materi Ekosistem - Sa’diah, Salsa Assiri Sa’diah; Chusni, Muhammad Minan; Kariadinata, Rahayu (International Journal of Science, Technology and Applications, 2025)
This study aims to determine the effect of applying the Problem Based Learning (PBL) model on students’ learning outcomes in ecosystem material. The background of this research is based on the low learning outcomes of students due to teacher-centered and memorization-oriented learning methods. The PBL model was chosen because it emphasizes active student involvement in solving real-world problems, thereby enhancing conceptual understanding and critical thinking skills. This research employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest design. The research subjects consisted of 33 eleventh-grade students who participated in biology learning using the PBL model. The research instrument was a learning achievement test administered before (pretest) and after (posttest) the implementation of the PBL model. Data analysis was conducted using the Paired Sample t-Test with the aid of SPSS version 25. The results showed that the average student learning score increased from 60.42 before the implementation of PBL to 82.61 after it. The t-test results indicated a significance value of 0.000 < 0.05, meaning there was a significant difference between learning outcomes before and after the treatment. The average N-Gain score of 56.36% indicated a moderate category, showing that the PBL model was effective in improving student learning outcomes.Thus, it can be concluded that the Problem Based Learning model has a positive and significant effect on improving students’ learning outcomes in ecosystem material. This model is effective as an alternative innovative learning strategy that encourages student activeness and conceptual understanding.